The Calypso hydrothermal vent field: The seafloor expression of an active submarine low-sulphidation epithermal system, Bay of Plenty, New Zealand - Hocking, Michael W. A (University of Ottawa (Canada), 2007)
The Taupo Volcanic Zone (TVZ) is an area of extensive volcanism and geothermal activity in the North Island of New Zealand. The Calypso Hydrothermal Vent Field (CHVF) is located in an offshore extension of the TVZ on continental shelf, approximately 10 km southwest of the White Island subaerial volcano, at 180-200 m water depth in the Bay of Plenty, New Zealand. Active, moderate temperature (up to 201°C) hydrothermal venting is contained within the Whakatane Graben, a northeast trending depression that has been partially filled by tephra from regional, subaerial volcanic eruptions. Venting of hydrothermal fluid through the volcaniclastic material has led to a varied and geographically distinct assemblage of alteration mineral phases in 4 vent fields in an area of approximately 50 km2. Carbon dioxide is the primary gas phase measured at active vent sites; sulfur is present as reduced H2S gas. The North Vent Field (NVF) is the original site of hydrothermal venting reported at Calypso. Weakly lithified volcaniclastic material recovered from this site has been altered primarily to montmorillonite, a dioctahedral smectite clay; minor mixed-layer clays were also detected. Native sulfur is spatially associated with the pervasively clay-altered samples, and is observed cementing volcaniclastic particles and filling primary pore spaces. Anhydrite mounds were also observed in the NVF. The principal hydrothermal alteration phase at the Southeast Vent Field (SEVF) and the Southwest Vent Field (SWVF) is amorphous silica which has filled the pore spaces between volcaniclastic particles and has overprinted early barite, minor clay, and native sulfur mineral phases. Cinnabar, stibnite, and amorphous arsenic sulfides form crusts on the outer surfaces of the samples as well as filling fractures, and forming inclusions within pyrite-silica veins. Textural relationships indicate volatile metal As, Sb, and Hg deposition is contemporaneous with silica precipitation. Clay-altered, sulfur-rich samples were also recovered from the Southeast and Southwest Vent Fields (SEVF, SWVF) but are volumetrically subordinate to the silica alteration facies. Several volcaniclastic samples from this site contained liquid hydrocarbon and charcoal fragments. A similar juxtaposition of alteration phases is observed in active geothermal environments in the subaerial portion of the TVZ (e.g., Waiotapu, Broadlands-Ohaaki). Where fluid conduits intersect the surface, near-neutral pH, chloride water will precipitate silica sinter with elevated volatile metal concentration +/- precious metals. Sinter deposits are characterized by a terraced morphology of opal precipitates and define the paleosurface in fossil epithermal systems. Such deposits have not been reported in the submarine environment. However, locations with high silica concentration, "sinter-like" material, and anomalous Hg-Sb-As concentrations have been described. At the Calypso field volcaniclastic material is cemented by amorphous silica similar to the silicified stratigraphy observed below silica sinter in some fossil epithermal deposits. The CO2 and H2S gas present in the hydrothermal fluid rise to areas of elevated topography peripheral to the sinter. Mixing of CO2 with water creates carbonic acid, and oxidation of H 2S may produce native sulfur and sulfuric acid; the extent of these reactions is limited by the availability of oxygen. In subaerial epithermal systems, the formation of sulfuric acid, and in turn advanced argillic steam-heated alteration, is limited to the vadose zone, where there is sufficient oxygen to produce sulfuric acid. In the absence of atmospheric oxygen, the production of sulfuric acid in submarine environments is similarly limited, and this explains the absence of aluminous clay minerals and alunite in the Calypso samples. Disproportionation of SO2(g) to H2SO4 (aq) does, however, create advanced argillic alteration in some higher-temperature submarine volcanic-hydrothermal systems (e.g., Brothers Volcano, de Ronde et al., 2005).